Contribution to the knowledge of the earthworm fauna of Turkey with description of three new species (Clitellata: Megadrili) - Szederjesi, Tímea; Dányi, László; Kaydan, Mehmet Bora; Csuzdi, Csaba (Zootaxa, 2018)
During a recent survey, 29 earthworm species were collected from different parts of Turkey, 27 of which belong to the family Lumbricidae, one to Acanthodrilidae and one to Megascolecidae. Dendrobaena proved to be the most speciose genus with 12 recorded species including two species new to science, Dendrobaena pavliceki and Dendrobaena taurica spp. nov. In addition a third new species was also found belonging to the East Mediterranean genus Healyella: Healyella zicsii sp. nov. From the species recorded earlier for Turkey, D. fridericae uludagi Omodeo & Rota, 1991 and He. boluana Omodeo & Rota, 1989 were found for the first time since the original description. With these new records the number of earthworm species recorded for Turkey is raised to 84.